PEMANFAATAN BUAH LOKAL DALAM RANGKA PEMBUATAN MINYAK KELAPA MURNI (VCO/VIRGIN COCONUT OIL) DI DESA TIAL KABUPATEN MALUKU TENGAH - A Netty Siahaya; Chaterina Bijang; Sherly J. Sekewael; I Wayan Sutapa (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The community service program aims to increase the economic value of coconut fruit through the production pf the processed coconut into virgin coconut oil with the target being women. Empowerment of women families in the Tial Vilage who are economically unproductive people (ordinary people). The targets are set by considering the efficiency and intensity of program implementation. Participants who are the group of housewives with the types of problems handled include aspect of production and business management. The production aspect is by training women for family welfare empowerment to produce virgin coconut oil (VCO) without healting with the hel of enzymes sourced from the use og local fruits, namely pineaplles and papaya. Meanwile, business management is planned by cooperating with cooperatives, stalls, shops,traders in markets, and supermarkets for marketing. Inessence, this activity is expected to be a solution to the problems faced by the community through an integrated approach, in order to increase the economic value of coconuts which are still not optimally utilized.